The Use of Species Distribution Modelling and Landscape Genetics for Tsetse Control - (:unkn) unknown (My University, 2021)
Trypanosomosis is one of the major constraints to rural development in sub-Saharan Africa. Studies of the species distribution and landscape genetics allows for targeting tsetse-infested areas and optimizing the management of tsetse fly populations. In this chapter, a review is provided on 1) available spatial tools and landscape genetics, 2) the use of tsetse distribution models to rank populations according to their level of isolation to assist identifying populations that can be targeted for eradication, and 3) the use of tsetse distribution models to optimize tsetse control efforts within an area-wide integrated pest management context.
Keywords: African Research